The Air We Breathe: Exploring the multifaceted impacts of Air Pollution on health and disease - Górski, Mateusz; Bychowski, Mateusz; Kwaśna, Julia; Załęska, Adrianna; Kaźmierczyk, Izabela; Lenart, Kacper; Homza, Michał; Zakrzewska, Natalia; Bednarek, Szymon; Kulicka, Joanna (Journal of Education, Health and Sport, 2024)
Background: Air pollution poses a significant global health risk, affecting a wide range of conditions, including skin aging, atopic dermatitis, cardiovascular diseases, respiratory disorders, and cancer. Recent studies reveal its role in accelerating aging and exacerbating chronic conditions through mechanisms like oxidative stress and systemic inflammation. However, gaps remain in understanding pollutant-specific effects and their cumulative impact on health. Methods: This review synthesizes findings from recent studies examining the effects of air pollution on skin and systemic health. A comprehensive analysis was conducted across multiple health conditions, with a focus on pollutant-specific mechanisms, including oxidative stress, DNA damage, immune dysregulation, and inflammatory responses. Results: Findings highlight strong correlations between exposure to pollutants, such as PM2.5, SO2, NOx, and VOCs, with adverse health outcomes. Pollutants exacerbate conditions like wrinkles, atopic dermatitis, thrombosis, and lung cancer. Interestingly, some pollutants, like ozone, showed mixed effects on specific skin conditions, emphasizing the need for nuanced analysis. Conclusion: Understanding the multifaceted impact of air pollution underscores the urgent need for targeted interventions and policies to mitigate health risks. Further research is essential to develop precise strategies to address the pollutant-specific effects and protect vulnerable populations.